LEADERSHIP OF ERASMUS MUNDUS PHD STUDENTS IN MULTICULTURAL SOCIETIES: DEFINING AND BUILDING A COMPETENCE - Ielyzaveta Panchenko (Pavlo Tychyna Uman State Pedagogical University, 2018)
This paper explores leadership from the standpoint of social constructivism. From this point, leadership is a complex notion that is studied in different ways and requires different definitions depending on the sphere, social circle, and situation where it is needed. It consists of knowledge, skills, and attitudes, which are formed and developed in the zone of proximal development - under assistance and in the process of communication. Four questions guided the investigation:  Does the understanding of leadership depend on the cultural background? How is the understanding of leadership formed in a multicultural environment? How is leadership addressed in the Erasmus Mundus programme? As there is no universal definition, the author developed a definition of Leadership of Erasmus Mundus PhD students. For Erasmus Mundus PhD students of AMU, leadership is the interaction between leaders and followers among scholars educated at Adam Mickiewicz University of Poznan, that leads to positive changes in development of countries and reaching European standards. As it suggests, there should be three sets of leadership expression: ability to interact, ability to learn, ability to change.  The focus group with Erasmus Mundus PhD students and the questionnaire for the alumni address the above mentioned. The findings prove that though cultural background influences some shades of understanding the notion of leadership, "schemas" of leadership of representatives of different social groups have more in common, than differences. The main leadership skill for representatives of all the studied nationalities is dealing with people. The importance of other skills differs depending on the nationality of a person. As to the specifics of forming understanding of leadership in a multicultural environment, it appears to be much more complex than the one in a monocultural environment. The Erasmus Mundus participants are all the time exposed to situations when they require assistance, and receive this assistance from people of various nationalities and positions. All those people become models of leaders that form their multicultural and multileveled understanding of leadership. As leadership consists of knowledge, skills, and attitudes, the authors explain how the Erasmus Mundus programme influences all of them: during the programme, knowledge is formed in the zone of proximal development, which is, from the standpoint of social constructivism, the best way to gain and retain knowledge; during the programme PhD students find positive changes in their personal skills, as well as gain some new ones, which can be proved by the words of the focus group interview participants; the atmosphere of AMU university provides good conditions for interaction and learning, also promotes personal changes of the participants, and motivates them to change their societies, forming their positive attitude to leadership and making them act like leaders after the programme, providing those changes.